2018
DOI: 10.1007/s10620-018-5111-7
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of ABL2 Suppresses Apoptosis in Gastric Cancer

Abstract: All the data showed that high expression of ABL2 suppresses apoptosis through Ras/Erk and PI3K/AKT signaling pathway in GC cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…As a member of the Abelson family, ABL2 has been confirmed to exert a carcinogenic effect in different kinds of cancers. For example, high expression of ABL2 is identified in gastric cancer cells and suppresses cell apoptosis in gastric cancer [ 45 ]. Besides, up-regulation of ABL2 is reported to predict poor prognosis of hepatocellular carcinomas and accelerate cell migration and invasion [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the Abelson family, ABL2 has been confirmed to exert a carcinogenic effect in different kinds of cancers. For example, high expression of ABL2 is identified in gastric cancer cells and suppresses cell apoptosis in gastric cancer [ 45 ]. Besides, up-regulation of ABL2 is reported to predict poor prognosis of hepatocellular carcinomas and accelerate cell migration and invasion [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…ABL2 belongs to Abelson family of non-receptor tyrosine kinase and regulates numerous cellular functions, such as cell viability, migration, apoptosis, and morphogenesis, in response to stimulation of cell surface receptors [ 31 , 32 ]. Liu et al demonstrated that ABL2 inhibited the cell apoptosis of gastric cancer [ 33 ]. Xing et al reported that the upregulation of ABL2 contributed to unsatisfactory prognosis and facilitated cell migration and invasion in HCC [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially, HSPA6, G0S2, TNFAIP3, GEM, GADD45G, RND1, SERPINB2, and IL24 have come forward with their repressive roles in malignant features of some cancers [ 29 – 35 ]. However, some genes like ABL2, EFNA1, CCL20, CXCL3, BCL2A1, IL20, and IL8, support cancer progression and they have already been highlighted as indicators of poor prognosis or suggested as potential therapeutic targets [ 36 40 ]. This finding suggests that upregulated anti-cancerous genes override the effects of upregulated cancerous genes when considering MAL-II previously demonstrated effects [ 7 ] on ATCCs.…”
Section: Discussionmentioning
confidence: 99%